Anatomy of the transgressive depositional system in a sediment-rich tide-dominated estuary: The paleo-Yangtze estuary, China. (November 2020) - Su, Jianfeng; Fan, Daidu; Liu, J. Paul; Wu, Yijing
Abstract: Sediment-rich tide-dominated estuary is generally considered nonexistent or ephemeral under the stable sea-level condition, given the rapid transition to a deltaic system after massive sediments dumping at the river mouth. The well-preserved transgressive sequence in the Yangtze paleo-valley represents an excellent location to examine the interplay between sediment supply, tide action, and sea-level change. To study the Yangtze paleo-valley geomorphological evolution and facies model, four 60-90-m long cores (YD0901, YD0902, YD0903, and CX03) were obtained. Lithological description, grain-size analysis, XRF core scanning, and AMS 14 C dating were carried out. The results show that the Yangtze incised valley evolved from a river channel system (before 14.6 ka), through a tidal river (14.6-13 ka), and a tide-dominated estuary (13-8 ka), to a shallow marine (after 8 ka). The paleo-Yangtze estuary displays inner section dominated by muddy heterolithic deposition and the outer section occupied by mud-rich tidal bars and channels, distinctly differing from the well-down small estuaries with sand predominance. A fining-upward facies succession was produced by migration of mud-rich tidal bars in response to post-glacial sea-level rise. These bars are potentially the predecessor of tidal sand ridges on the East China Sea shelf after they were progressively abandoned during the post-glacial sea-level rise and exposed to tidal and storm-wave reworking. This is the first facies model developed from a sediment-rich tide-dominated estuary. This study provides a best example to study evolution of tide-dominated mega-river systems in response to the post-glacial transgression. Highlights: The facies model of the paleo-Yangtze estuary, a mixed-energy estuary. Sea-level, tide and sediment supply shape the geomorphological evolution. The vast riverine sand supply and fluid mud layer form the muddy tidal sand bars. Estuarine tidal sand bars are the predecessor of tidal sand ridges on the shelf.